2020
DOI: 10.1101/2020.02.22.961102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Pumpless Microfluidic Neonatal Lung Assist Device for Support of Preterm Neonates in Respiratory Distress

Abstract: Premature neonates suffer from respiratory morbidity as their lungs are immature and current supportive treatment such as mechanical ventilation or extracorporeal membrane oxygenation (ECMO) cause iatrogenic injuries. A non-invasive and biomimetic concept known as the "artificial placenta" would be beneficial to overcome complications associated with the current respiratory support of preterm infants. Here, a pumpless oxygenator connected to the systemic circulation supports the lung function to relieve respir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…69,70 More recently, microfluidic prototypes supporting blood flows of 100-200 ml/min have been reported. 30,31,71 These devices comprise multilayer stacks of microchannel networks, with stack heights of 8-56 layers vertically integrated by blood distribution manifolds. While these larger-scale devices are promising and approach the flow rates required for carbon dioxide removal or neonatal ECMO, significant further scale-up would be required for full respiratory support for adults, both in the size of the layers and the number of layers in the stack.…”
Section: Microfluidic Membranes For Lung-assist Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…69,70 More recently, microfluidic prototypes supporting blood flows of 100-200 ml/min have been reported. 30,31,71 These devices comprise multilayer stacks of microchannel networks, with stack heights of 8-56 layers vertically integrated by blood distribution manifolds. While these larger-scale devices are promising and approach the flow rates required for carbon dioxide removal or neonatal ECMO, significant further scale-up would be required for full respiratory support for adults, both in the size of the layers and the number of layers in the stack.…”
Section: Microfluidic Membranes For Lung-assist Devicesmentioning
confidence: 99%
“…These performance metrics have been evaluated in laboratory/in vitro studies as well as in short-term preliminary animal experiments ranging from 2 kg piglets to 40 kg farm swine. 31,59,72,73 Ultimately, hemocompatibility studies will need to compare microfluidic oxygenators to HFM devices in controlled animal studies lasting for periods of 24 h or longer.…”
Section: Microfluidic Membranes For Lung-assist Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2,3 ] In late‐preterm and term infants, extracorporeal membrane oxygenation (ECMO) could be an alternative choice of treatment, but ECMO requires central vascular access by surgery, as well as their high priming volume and external pump for perfusion are not suitable for neonatal infants. [ 4 ] Through the experiment by Dabaghi et al., [ 1 ] we learned that LAD has the characteristics of high‐performance, and pumpless. In addition, an important element of LAD is that the newborn will continue to breathe while the LAD provides additional gas exchange and allows the lungs to heal.…”
mentioning
confidence: 99%
“…operated a microfluidic, artificial placenta‐type neonatal lung assist device (LAD) on a newborn piglet with respiratory distress. [ 1 ] Results from the piglet experiments revealed the effectiveness of this LAD in gas exchange without complications. The authors indicated that the LAD has a potential application as a biomimetic artificial placenta to support the respiratory needs of preterm neonates.…”
mentioning
confidence: 99%